N-Acetylcysteine: A Review of Clinical Usefulness (an Old Drug with New Tricks) - Gerry K. Schwalfenberg (Journal of Nutrition and Metabolism)
Objective. To review the clinical usefulness of N-acetylcysteine (NAC) as treatment or adjunctive therapy in a number of medical conditions. Use in Tylenol overdose, cystic fibrosis, and chronic obstructive lung disease has been well documented, but there is emerging evidence many other conditions would benefit from this safe, simple, and inexpensive intervention. Quality of Evidence. PubMed, several books, and conference proceedings were searched for articles on NAC and health conditions listed above reviewing supportive evidence. This study uses a traditional integrated review format, and clinically relevant information is assessed using the American Family Physician Evidence-Based Medicine Toolkit. A table summarizing the potential mechanisms of action for N-acetylcysteine in these conditions is presented. Main Message. N-acetylcysteine may be useful as an adjuvant in treating various medical conditions, especially chronic diseases. These conditions include polycystic ovary disease, male infertility, sleep apnea, acquired immune deficiency syndrome, influenza, parkinsonism, multiple sclerosis, peripheral neuropathy, stroke outcomes, diabetic neuropathy, Crohn’s disease, ulcerative colitis, schizophrenia, bipolar illness, and obsessive compulsive disorder; it can also be useful as a chelator for heavy metals and nanoparticles. There are also a number of other conditions that may show benefit; however, the evidence is not as robust. Conclusion. The use of N-acetylcysteine should be considered in a number of conditions as our population ages and levels of glutathione drop. Supplementation may contribute to reducing morbidity and mortality in some chronic conditions as outlined in the article.